Fluoride-Free Hiyama Coupling Reaction Catalyzed by Linear Polystyrene-Stabilized PdO Nanoparticles in Water: Specific Reactivity of PdO Nanoparticles over Pd Nanoparticles - Ohtaka, Atsushi; Kotera, Takamasa; Sakon, Akira; Ueda, Kouhei; Hamasaka, Go; Uozumi, Yasuhiro; Shinagawa, Tsutomu; Shimomura, Osamu; Nomura, Ryôki (Synlett, 2016)
Linear polystyrene-stabilized PdO nanoparticles (PS-PdONPs) exhibited high catalytic activity for fluoride-free Hiyama coupling reaction of aryltrimethoxysilanes with a variety of bromoarenes under air in water. In contrast, no desired coupling product was obtained from the Hiyama coupling reaction using linear polystyrene-stabilized Pd nanoparticles (PS-PdNPs) as a catalyst. The different reactivities of PdONPs and PdNPs will be discussed.
Keywords: polystyrene; PdO nanoparticles; Pd nanoparticles; Hiyama coupling reaction; water